Kompetensi Item Analysis dan Korelasinya terhadap Profesionalitas Guru SMA/SMK Katolik di Kota Manado - Imbang, Jearne Felix; Wehantow, Jeniver Karpiati Gabriela (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
This study aims to: describe (1) item analysis competency and (2) professionalism of Catholic high school/vocational high school teachers in Manado City; (3) determine how big the correlation/relationship is between item analysis competency and the professionalism of Catholic high school/vocational high school teachers in Manado City; (4) describe efforts to improve item analysis competency as part of the professionalism of Catholic high school/vocational high school teachers in Manado City. The method used is a mix method. Obtaining descriptive data related to research objectives (1), (2) and (4) used qualitative methods; continued with the application of quantitative methods to obtain data related to research objectives (3). The data sources in this study were the principals and teachers of Catholic high schools/vocational high schools in Manado City totaling 121 people with 93 samples. The data collection technique for the qualitative method used interview techniques as well as observation and documentation; determining the source of interview data used purposive sampling. The results of the qualitative study of item analysis competency showed that some teachers knew and were able to make item analysis, but there were also those who did not understand and did not apply it. Quantitative results on how big the correlation of item analysis competency with teacher professionalism with a sample of 93 people from 121 populations showed significant results below 0.05, so it is included in the very good category. The percentage of variable X (item analysis competency) is 85% and variable Y (teacher professionalism) is 82%. The influence of X on Y is: 0.432; this result can be interpreted that the correlation of item analysis competency with teacher professionalism is in the moderate relationship category. This means that there are still other factors whose relationship category with Y is lower or higher, but these factors were not examined in this study.